Internal Governance Mechanisms and Corporate Carbon Transparency: Evidence from Indonesian Mining Companies - Ravololonirina Natacha; Susi Sarumpaet (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Climate change has increased expectations for companies to be transparent about their environmental impact, particularly carbon emissions. Carbon disclosure enables stakeholders to assess how firms manage environmental and climate-related risks, yet transparency remains uneven, especially in high-impact industries such as mining. This study examines the influence of internal governance mechanisms: board size, independent commissioners, and performance-based executive compensation on carbon emission disclosure among mining companies listed on the Indonesia Stock Exchange during 2022–2024. Using panel data from 53 firms and a fixed-effects regression model, the results show that board size has a significant negative effect on carbon transparency, independent commissioners have no significant influence, and executive compensation has a positive but relatively weak effect. These findings highlight the complex role of governance structures in shaping environmental reporting and provide insights for policymakers and managers seeking to improve climate-related disclosure.